From patient days to weighted patients: Developing better nursing workload measures. Issue 12 (December 2022) - Fogel, Paul; Hullet, Amanda; Pauls, Lori
Abstract : Traditional workload measures for in-patient nursing units based on patient days, a once-a-day midnight census, fail to account for other relevant factors. The authors outline how to build a system that's responsive to both patient volume and acuity throughout the day and matched to proper patient-to-nurse staffing ratios.